"Bless Thy Blue Panorama …": The Cosmopersonalism and Historiosophic Irony of Maximilian Voloshin. Issue 4 (4th July 2018) - Soloviev, Erikh Yu.
Abstract : The year 2017 is not only the centennial of two Russian revolutions, but also an anniversary for one of its most prominent witnesses, the artist, poet, and essayist Maximilian A. Voloshin (1877–1932). Voloshin's highly original philosophical viewpoint is best defined as "cosmopersonalism." Unlike the standard representatives of Russian cosmism (Vladimir I. Vernadsky, Alexander L. Chizevsky, Nikolai F. Fedorov), all of whom gravitated toward a collectivist, ensemble interpretation of the deepest foundations of human subjectivity, Voloshin insists on the eternal, cosmically given existence of each individual I. A cosmopersonalist philosophical belief protects from bias in politics and ideology and makes possible an ironically playful attitude toward all natural-historical processes, even catastrophic ones. During the revolutionary years, Voloshin wrote a number of works on Russia that belong to the genre of eschatological prophecy. They are contradictory, they belie one another, and, each being a tragic work when considered separately, they can be interpreted in the aggregate as a detached mental experiment in missionary historiosophical constructions (on hopes and premonitions, utopias and anti-utopias). The article argues that Voloshin outgrew eschatology sometime in the mid-1920s and began confessing a stoic version of the philosophy of "small deeds, " based on the idea that every human being has universal dignity.